The Relationship between Thinking Patterns and Academic Achievement in the Subject of Social Sciences - Fahira, Wina Roza; Putri, Melliyati; Setiawati, Merika (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This study aims to investigate the relationship between students' thinking patterns and their academic achievement in the subject of Social Sciences. The research methodology involves conducting the Lilliefors Normality Test to ensure the data follows a normal distribution and the Product Moment Correlation Test to analyze the correlation between variables. The sample selection is based on random sampling technique using the Slovin Formula, resulting in a sample size of 32 students. The thinking patterns variable is measured using a questionnaire distributed to the selected students as research respondents, while academic achievement is obtained from the students' report card scores. The analysis results reveal a significant and strong positive relationship between students' thinking patterns and their academic achievement in the 8th grade at SMPN 3 Kota Solok. This finding suggests that students who exhibit favorable thinking patterns are more likely to achieve higher academic performance in Social Sciences. Therefore, it is recommended for educators to pay attention to fostering and enhancing students' thinking patterns to promote better academic outcomes. This study contributes to the existing body of knowledge by providing empirical evidence on the importance of thinking patterns in relation to academic achievement in the field of Social Sciences.┬á